Answer:
a = -10
Explanation:
Simplifying
7 + 4(2a + 15) = -13
Reorder the terms:
7 + 4(15 + 2a) = -13
7 + (15 * 4 + 2a * 4) = -13
7 + (60 + 8a) = -13
Combine like terms: 7 + 60 = 67
67 + 8a = -13
Solving
67 + 8a = -13
Solving for variable 'a'.
Move all terms containing a to the left, all other terms to the right.
Add '-67' to each side of the equation.
67 + -67 + 8a = -13 + -67
Combine like terms: 67 + -67 = 0
0 + 8a = -13 + -67
8a = -13 + -67
Combine like terms: -13 + -67 = -80
8a = -80
Divide each side by '8'.
a = -10
Simplifying
a = -10